Integrating manganese oxide nanoparticles with functionalized carbon nanotubes on carbon cloth to serve as a stable anode for high-capacity Li-ion cells - Merin K. Wilson; Dhanya P. Jacob; Aldrin Antony; M.K. Jayaraj; S. Jayalekshmi (Next Energy)
Globally, energy demands are massive, and environmental issues are rising against our sustainability. To maximize the use of renewable energy sources, development of efficient energy storage systems is mandatory. Lithium-ion batteries (LIBs) play an indispensable role in powering portable devices and electric vehicles, due to their high specific capacity and long cycle life. Manganese oxide (Mn3O4) is an environmentally friendly anode active material with high theoretical specific capacity of 936 mAh g−1 for applications in Li-ion cells.In the present work, Mn3O4-functionalized carbon nanotubes (FCNT) nanocomposite, coated on carbon cloth (CC) current collector and termed as Mn3O4-FCNT @CC, is used as the anode material. Li-ion coin cells based on this nanocomposite anode show discharge capacity of 1371mAhg−1 and charge capacity of 1141mAhg−1 at current density of 100 mA g−1 with initial Coulombic efficiency of 83%. After 70 cycles, the charge-discharge capacities of the cells are 953mAhg−1 and 958mAhg−1, respectively, with capacity retention of 91% at current rate of 100 mA g−1. These cells are found to deliver reversible charge capacity of 575mAhg−1 after 100 cycles at 1C (∼1 A g−1) and offer prospects of stable operation at high current rates.